Stopping power of cluster ions in a free-electron gas from partial-wave analysis - Matias Da Silva, Flávio (2018)
A nonlinear model for the stopping power of cluster ions based on partial-wave analysis is developed through the generalization of the induced density approach (IDA) model for the interaction of homo- and heteronuclear molecular ions with a free-electron gas (IDAMol). We apply IDAMol to the energy loss of H2+ dimers in SiO2 and Al2O3, where we find that the results are consistent with established linear (dielectric) models at higher speeds, as expected for small perturbations (small values of the projectile charge or high velocities). Specifically at low projectile energies, however, it is important that IDAMol goes beyond perturbation theory. This feature appears to be central for a good description of negative and positive vicinage effects, a measure of the deviation from the independent-atom model. The focus of this work, however, is the investigation of enhanced nonlinear effects. Here we present experimental results for a heteronuclear cluster ion namely HeH+ on Al2O3, in the energy range of few tens of keV/u using the medium energy ion scattering technique. The IDAMol results are corroborated by the experimental data and time-dependent density-functional calculations for this case. Strong nonlinearities are observed for the energy loss of the fragment H+ due to the higher charge of its He companion.